Analysis of the Application of Materiality by KAP X to the Vouching Procedure for Revenue and Operating Expense Transactions of PT Z - Hutami, Anugrah Fani Siwi; Sumiadji, Sumiadji; Asdani, Andi (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
This study aims to comprehensively examine the application of the concept of materiality and the vouching procedure in the financial statement audit process at PT Z by Public Accounting Firm (KAP) X. This study uses a qualitative approach with a case study method, in which data is collected through in-depth interviews, documentation, and review of relevant audit working papers. The results show that KAP X sets materiality thresholds based on a quantitative approach, taking into account key financial indicators such as total assets and income, as well as qualitative factors that could potentially influence the decision-making of financial statement users. Vouching procedures are carried out in a structured manner on accounts that are considered material and high risk in order to obtain reliable audit evidence. These findings indicate that the synergy between the application of proportional materiality and targeted vouching can improve the effectiveness of audit procedures and the quality of testing the fairness of financial statements as a whole.